Design, synthesis and pharmacological evaluation of some pyrazolopyrimidin-6(7H)-ones and tricyclic 8-oxo-dihydrooxazolopyrazolopyrimidin-9-ium chloride derivatives - Kulshrestha A.; Das N.; Banerjee A.G.; Shrivastava S.K. (My University, 2025)
In the present study, some pyrazolopyrimidin-6(7H)-ones and tricyclic 8-oxo-dihydrooxazolopyrazolopyrimidin-9-ium chloride derivatives were synthesized and tested for anti-inflammatory and analgesic activity and assessment of acute ulcerogenic propensity as compared to the standard drug indomethacin. Some of the compounds (2c–2e; 3c–3e) showed appreciable anti-inflammatory–analgesic activity at the evaluated equimolar dose with lower ulcerogenic profile when compared with the standard. Compounds containing fused dihydrooxazolo ring (3e) system were found to be more active than their corresponding congener pyrazolopyrimidine. © 2014 King Saud University